Balancing Innovation and Risk: Cybersecurity Concerns in Cloud Adoption Among Accountants - Iis Solihat (International Journal of Economic and Business Research, 2026)
The rapid advancement of digital technology has significantly transformed the accounting profession, particularly through the adoption of cloud computing. While cloud accounting offers substantial benefits such as improved efficiency, real-time data access, and cost-effectiveness, it also introduces critical cybersecurity risks that may hinder its adoption. This study aims to examine how accountants balance the benefits of innovation with cybersecurity concerns in adopting cloud-based accounting systems. This research employs a qualitative approach using focus group discussions and in-depth interviews with accounting professionals. The analysis is guided by the cybersecurity risk taxonomy framework, encompassing individual actions, system and technology failures, internal process weaknesses, and external threats. Thematic analysis is applied to identify key patterns and insights related to cloud adoption behavior. The findings reveal that although cloud accounting enhances financial reporting efficiency, accuracy, and timeliness, cybersecurity concerns particularly data breaches, unauthorized access, and system vulnerabilities remain significant barriers to adoption. Additionally, perceived trust and cybersecurity awareness play a crucial mediating role in influencing adoption decisions. Higher levels of trust and security awareness are associated with greater acceptance and effective implementation of cloud accounting systems. This study contributes to the literature by integrating perspectives of cybersecurity risk and trust in understanding cloud accounting adoption. Practically, the findings highlight the importance of strengthening cybersecurity frameworks, enhancing user awareness, and implementing comprehensive risk management strategies to support secure and sustainable adoption of cloud technologies in the accounting profession.